PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS V SD NEGERI 060912 MEDAN DENAI: Penelitian Tindakan Kelas - Ladimir Putin Simbolon; Marah Doly Nasution; Sri Suharni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve student learning outcomes in the subject of Natural and Social Sciences (IPAS) through the implementation of the Problem Based Learning (PBL) model in Class V-A of SD Negeri 060912 Medan Denai. The background of this research is the low learning outcomes of IPAS due to the dominance of lecture methods and the lack of innovative learning models. This research is a Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. Each cycle consists of planning, action, observation, and reflection stages. The results show that the implementation of the PBL model significantly improves student learning outcomes. In the pre-cycle, the average student score was 60 with a mastery level of 45%. After implementing PBL, the average score increased to 71 with 75% mastery in Cycle I, and further increased to 81.5 with 85% mastery in Cycle II. Moreover, students' learning motivation and activeness also improved through group discussions, solving real-world problems, and the use of interactive PowerPoint media. Based on these results, it can be concluded that the PBL model is effective in enhancing the learning outcomes of fifth-grade students in IPAS.